Preparation method of biomass graphitized porous carbon for lead-carbon battery and lead-carbon battery
By using the activation-catalyst formed by compound formation, pore formation activation and catalytic graphitization are performed simultaneously, biomass graphitized porous carbon for lead-carbon batteries with high specific surface area and appropriate micromesoporous ratios is prepared, which solves the problem of irreversible sulfateization of traditional lead-acid batteries under high-rate charging and discharge conditions, and significantly improves the hydrogen evolution overpotential and cycle capacity retention rate of the battery.
Patent Information
- Application Number
- CN202411747604.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional lead-acid batteries are prone to irreversible sulfate under high-rate charging and discharging conditions, resulting in short battery life. The hydrogen evolution overpotential of existing biomass graphitized porous carbon is low and has poor conductivity, requiring high-temperature graphitization treatment, and the catalyst is highly corrosive.
The biomass was impregnated by the activation catalyst formed by the compounding of phosphoric acid, imidazolium tetrachloroferrate, ferrate and the permeability promoter polyoxyethylene fatty acid ester. Pore-making activation and catalytic graphitization were synchronized to prepare biomass graphitized porous carbon for lead-carbon batteries with high specific surface area and appropriate micromesoporous ratio.
The hydrogen evolution overpotential of lead-carbon batteries is significantly improved, the hydrogen evolution reaction of the negative electrode plate is delayed, the circulation capacity retention rate is improved, the battery performance is slowed down, and the preparation process is green and efficient.
Smart Images

Figure CN119612512A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead-carbon batteries, and in particular relates to a method for preparing biomass graphitized porous carbon for a lead-carbon battery and a lead-carbon battery. Background Art
[0002] In order to alleviate the energy crisis and environmental pollution, countries around the world have begun to develop new energy vehicles, and hybrid vehicles are a very important part of them. Traditional lead-acid batteries have been used in light hybrid vehicles due to their low price and good high current discharge performance. However, the negative electrode of traditional lead-acid batteries is prone to irreversible sulfation under high rate charge and discharge (HRPSoC) conditions, which makes the life of lead-acid batteries very short. Lead-carbon batteries that combine the advantages of supercapacitors and lead-acid batteries can effectively delay the irreversible sulfation of the negative electrode. The positive electrode of the lead-carbon battery is the same as that of ordinary lead-acid batteries, both of which are PbO2, and its negative electrode is a mixed electrode of lead and carbon materials. However, the hydrogen evolution potential of carbon materials is much lower than that of lead, and the hydrogen evolution current is much higher than that of lead. Therefore, the addition of carbon materials exacerbates the hydrogen evolution phenomenon of the negative electrode. Hydrogen evolution not only causes serious loss of electrolyte during the cycle, but also affects the charging efficiency of the battery, destroys the structure of the negative plate, and increases the internal resistance of the negative plate, so that the performance of the battery decays quickly. Therefore, it is particularly important to increase the hydrogen evolution overpotential of carbon materials and delay the hydrogen evolution reaction of the negative electrode plate.
[0003] Biomass is an abundant source, and it is economically beneficial to use biomass as raw material to prepare carbon materials for lead-carbon batteries. In the prior art, biomass raw materials are generally prepared by chemical activation, such as using potassium hydroxide, potassium carbonate, sulfuric acid or zinc chloride as an activator to activate and pore the raw materials to obtain porous carbon. However, the porous carbon obtained by this method generally has a too low hydrogen evolution overpotential; and the porous carbon obtained by this method generally has an amorphous structure and poor electrical conductivity. In practical applications, it is also necessary to perform high-temperature graphitization treatment to improve its electrical conductivity, and the catalyst transition metal nitrate or chloride used in the graphitization treatment is highly corrosive. Therefore, it is very important to develop biomass graphitized porous carbon with a high hydrogen evolution overpotential and a green and efficient preparation process.
[0004] In the prior art, the modification of biomass carbon is mainly used to improve the hydrogen evolution overpotential. For example, activated carbon is introduced with materials with high hydrogen evolution overpotential, such as silver oxide, zinc oxide or rare earth oxide, by blending, loading, coating or in-situ method; and activated carbon is doped with heteroatoms to increase the specific surface area and multi-porous structure of porous carbon, such as the specific surface area should be within an appropriate range, and the ratio of micropores to mesopores should be appropriate. The above methods either have limited improvement in hydrogen evolution overpotential or are complicated in process; and high-temperature graphitization treatment is still required in the subsequent process. In the prior art, the amount of graphitization catalyst used is generally large, and the cost is also high. If activated pore formation and catalytic graphite can be combined, it is possible to increase the hydrogen evolution overpotential of porous carbon, and the preparation process is green and efficient.
[0005] Chinese patent CN107265436A proposes a method that uses only potassium ferrate as a pore-forming agent and a graphitization catalyst without adding any other activators and catalysts. During the implementation of the patented method, potassium ferrate is dissolved in water and then mixed with the carbon source precursor biomass. However, potassium ferrate is not stable in neutral water and quickly becomes turbid to generate iron hydroxide, which is not conducive to the highly dispersed mixing of the catalyst and the carbon source precursor, and is bound to have a negative impact on the graphitization and porosity effects. Summary of the invention
[0006] In view of the above problems, the purpose of the present invention is to provide a method for preparing biomass graphitized porous carbon for lead-carbon batteries. During the preparation process, activation pore formation and catalytic graphitization are carried out simultaneously, and the preparation process is green and efficient; and the prepared graphitized porous carbon is used as an additive in the negative electrode of a lead-carbon battery to effectively increase the hydrogen evolution overpotential, thereby inhibiting irreversible sulfation, and further improving the cycle performance of the lead-carbon battery under HRPSoC conditions.
[0007] The present invention provides the following technical solutions to solve the above technical problems:
[0008] A method for preparing biomass graphitized porous carbon for lead-carbon batteries comprises the following steps:
[0009] (S1) impregnation: the pretreated biomass is immersed in an impregnation solution, and then granulated and dried in sequence to obtain a preform; the impregnation solution is a mixed aqueous solution of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester prepared in a mass ratio of 100: (25-40): (15-35): (1-3);
[0010] (S2) heat treatment: heat treating the preform under an inert atmosphere, cooling, washing and drying after the heat treatment to obtain graphitized porous carbon;
[0011] (S3) oxidation: soaking the graphitized porous carbon in an oxidant solution, rinsing and drying after soaking to obtain an oxidized material;
[0012] (S4) Surface modification: The oxidizing material is mixed with melamine polyphosphate, heat-treated in an ammonia atmosphere, and then cooled and ground to obtain biomass graphitized porous carbon for lead-carbon batteries.
[0013] The present invention prepares biomass graphitized porous carbon for lead-carbon battery by impregnating pretreated biomass with an activation-catalyst formed by compounding phosphoric acid, imidazolium tetrachloroferrate, ferrate and a penetration enhancer polyoxyethylene fatty acid ester, and then heat treating, oxidizing and surface modifying. Imidazolium tetrachloroferrate is an ionic liquid and has good solubility for biomass raw materials. The inventors found that imidazolium tetrachloroferrate can synergistically activate biomass with phosphoric acid. The possible reason is that the imidazolium ring in imidazolium tetrachloroferrate has a certain force with the benzene ring in the biomass, thereby promoting the activation of the biomass raw material by phosphoric acid; at the same time, imidazolium tetrachloroferrate can catalyze graphitization together with ferrate. That is, imidazolium tetrachloroferrate plays a multi-functional role. The activation-catalyst formed by its combination with phosphoric acid, ferrate and penetration enhancer polyoxyethylene fatty acid ester realizes the simultaneous pore-forming activation and catalytic graphitization, and the preparation process is green and efficient; and the biomass graphitized porous carbon for lead-carbon batteries finally obtained has a high specific surface area, an appropriate micro-mesopore ratio, and a certain nitrogen content. It can be used as an additive in the negative electrode of a lead-carbon battery to effectively increase the hydrogen evolution overpotential.
[0014] Preferably, in step (S1), the impregnation solution is a mixed aqueous solution of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester prepared in a mass ratio of 100: (25-35): (20-30): (1-3).
[0015] Furthermore, in step (S1), the imidazolium tetrachloroferrate is at least one of 1-butyl-3-methylimidazolium tetrachloroferrate and 1-ethyl-3-methylimidazolium tetrachloroferrate.
[0016] Furthermore, in step (S1), the ferrate is at least one of potassium ferrate and sodium ferrate; and the polyoxyethylene fatty acid ester is at least one of ferrate 49 and ferrate 52. Polyoxyethylene fatty acid ester has good solubilization and wetting effects on biomass, and can enhance the activation ability of phosphoric acid and imidazolium tetrachloroferrate.
[0017] Furthermore, in step (S1), the pretreatment is to crush, wash and dry the biomass in sequence; the biomass is at least one of coconut shells, rice shells and walnut shells.
[0018] Furthermore, in step (S1), the ratio of the pretreated biomass to the impregnation liquid is 1 kg: (4-8) L, the concentration of the impregnation liquid is 25-40 wt %; the impregnation conditions are: temperature 60-80° C., time 2-4 h.
[0019] The granulation in step (S1) is to obtain columnar or spherical granules by a granulator, for example, by a plunger granulator, cutting into rods or strips with a diameter of 2 to 5 mm, such as 2 mm, 3 mm, 4 mm, and a length of 100 to 150 mm; by a needle granulator, spherical particles are formed, and the particle size can be 1.5 mm, 2 mm, 2.5 mm, 3 mm; the drying is drying in an oven at 100 to 150° C. for 24 to 36 hours.
[0020] Furthermore, in step (S2), the inert atmosphere has an oxygen content of less than 0.1%, such as nitrogen and / or argon; the heat treatment conditions are: heating to 1300-1800°C at a heating rate of 5-10°C / min in a graphitization furnace, and keeping warm for 2-4 hours; the washing is boiling in water for 30-60 minutes to remove residual phosphoric acid in the heat-treated material, so that the phosphoric acid in the heat-treated material is less than 200ppm, and the residual phosphoric acid can also be recovered for use in step (S1); the drying is drying to a moisture content of <5wt%, such as baking in an oven at 80-120°C for 24-36 hours.
[0021] Furthermore, in step (S3), the oxidant solution is 10wt% to 20wt% hydrogen peroxide or an oxidizing inorganic strong acid, and the oxidizing inorganic strong acid is 3 to 5 mol / L nitric acid and / or sulfuric acid.
[0022] Furthermore, in step (S3), the amount ratio of the graphitized porous carbon to the oxidant solution is 100g: (500-1000)mL; the soaking conditions are: temperature 40-60°C, time 2-6h; the rinsing is to rinse with water to neutrality to wash away the residual oxidant; the drying is to dry to constant weight, such as baking in an oven at 80-100°C for 24-36h. The graphitized porous carbon can increase the surface acidic functional groups and reduce the surface isoelectric point after oxidation, which is beneficial to the subsequent surface modification.
[0023] Furthermore, in step (S4), the mass ratio of the oxidizing material to the melamine polyphosphate is 100:(4-8). Melamine polyphosphate decomposes at 300-400°C to produce a large amount of ammonia and water, which can further increase the porosity of the graphitized porous carbon and reduce its packing density; on the other hand, the generated ammonia can also react with the graphitized porous carbon at high temperature to introduce pyridine, pyrrole and quaternary nitrogen-containing functional groups on its surface, that is, to prepare a graphitized porous carbon with a certain nitrogen content, but the nitrogen content should not be too high, otherwise it will affect the skeleton strength of the graphitized porous carbon.
[0024] Furthermore, in step (S4), the heat treatment conditions are: introducing ammonia into a horizontal induction furnace, heating the temperature to 850-950°C at a heating rate of 3-8°C / min, and keeping the temperature for 2-4h; the grinding is performed by using a jet grinder, and the particle size D50 after grinding is 6-10μm.
[0025] The present invention also provides a lead-carbon battery, the negative electrode material of which comprises the biomass graphitized porous carbon prepared by the above preparation method.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1) The present invention uses phosphoric acid, imidazolium tetrachloroferrate, ferrate and a polyoxyethylene fatty acid ester as a penetration enhancer to form an activation-catalyst for impregnating the pretreated biomass, and then heat-treating, oxidizing and surface-modifying to prepare biomass graphitized porous carbon for lead-carbon batteries. Imidazolium tetrachloroferrate can not only activate the biomass in synergistic effect with phosphoric acid, but also catalyze graphitization with ferrate; that is, imidazolium tetrachloroferrate plays a multi-functional role, pore-forming activation and catalytic graphitization are carried out simultaneously, and the preparation process is green and efficient.
[0028] 2) The biomass graphitized porous carbon for lead-carbon battery prepared by the present invention has the characteristics of high specific surface area, appropriate micro-mesoporous ratio, and nitrogen atom doping, wherein the specific surface area is up to 1500m 2 / g or more, microporosity of more than 25%, and mesoporosity maintained at 65% to 72%, and nitrogen content of more than 7%. The biomass graphitized porous carbon prepared by the present invention is used as a negative electrode additive for lead-carbon batteries, and the hydrogen evolution overpotential is significantly improved to more than 1.30V, thereby improving the cycle capacity retention rate, thereby slowing down the performance decay of the lead-carbon battery, and the 500 cycle capacity retention rate at 2C under HRPSoC reaches more than 91%. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the biomass graphitized porous carbon prepared in Example 1.
[0030] Figure 2 This is the X-ray diffraction spectrum of the biomass graphitized porous carbon prepared in Example 1.
[0031] Figure 3 This is the pore size distribution diagram of the biomass graphitized porous carbon prepared in Example 1. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific examples. Unless otherwise specified, the "parts" described in the examples of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0033] Example 1
[0034] (S1) Impregnation: The rice husk is mechanically crushed to 200 mesh, washed twice with water, and then placed in an oven at 90°C for 24 hours to obtain a pre-treated material; then 25 parts of 1-butyl-3-methylimidazolium tetrachloroferrate, 15 parts of potassium ferrate, and 1 part of a penetration enhancer, Mai Ze 49, are dissolved in 400 parts of a 25wt% phosphoric acid solution to form an impregnation solution (i.e., the mass ratio of phosphoric acid, 1-butyl-3-methylimidazolium tetrachloroferrate, potassium ferrate, and penetration enhancer, Mai Ze 49, is 100:25:40:1); then the pre-treated material is added to the impregnation solution at a dosage ratio of 1kg:5L, and impregnated in a kneader at 90°C for 3 hours to obtain a kneaded material; then the kneaded material is formed into spherical particles with a particle size of 2.5mm by a pin granulator, and dried in an oven at 95°C for 24 hours to obtain a prefabricated material;
[0035] (S2) Heat treatment: The preform is placed in a graphitization furnace, heated to 1300°C at a heating rate of 8°C / min under a nitrogen atmosphere, and kept at this temperature for 3 hours; after the heat treatment, it is naturally cooled to room temperature, boiled in water for 40 minutes, and baked in an oven at 100°C for 24 hours to obtain graphitized porous carbon;
[0036] (S3) Oxidation: 200 g of graphitized porous carbon was put into 1500 mL of 5 mol / L nitric acid and soaked at 50° C. for 4 h. After soaking, it was rinsed with pure water until neutral, and then baked in an oven at 90° C. for 24 h to obtain an oxidized material.
[0037] (S4) Surface modification: 100 g of the oxidizing material was mixed with 6 g of melamine polyphosphate, placed in a horizontal induction furnace, ammonia gas was introduced, the temperature was increased to 850° C. at a heating rate of 8° C. / min, and the mixture was kept at this temperature for 3 h. After the modification was completed, the mixture was naturally cooled to room temperature, and then ground with a jet mill to obtain biomass graphitized porous carbon for lead-carbon batteries with a particle size D50 of 7.2 μm.
[0038] The SEM image of the prepared biomass graphitized porous carbon for lead-carbon battery is shown in Figure 1 The X-ray diffraction spectrum is shown in Figure 2 The pore size distribution diagram is shown in Figure 3 shown.
[0039] Example 2
[0040] The rest is the same as Example 1, except that: in step (S1), the mass ratio of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester in the impregnation solution is 100:25:20:1, and finally a biomass graphitized porous carbon for lead-carbon batteries with a particle size D50 of 7.1 μm is obtained.
[0041] Example 3
[0042] The rest is the same as Example 1, except that: in step (S1), the mass ratio of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester in the impregnation solution is 100:30:20:1, and finally a biomass graphitized porous carbon for lead-carbon batteries with a particle size D50 of 6.9 μm is obtained.
[0043] Example 4
[0044] The rest is the same as Example 1, except that: in step (S1), the mass ratio of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester in the impregnation solution is 100:35:25:2, and finally a biomass graphitized porous carbon for lead-carbon batteries with a particle size D50 of 6.8 μm is obtained.
[0045] Example 5
[0046] The rest is the same as Example 1, except that: in step (S1), the mass ratio of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester in the impregnation solution is 100:35:30:2, and finally a biomass graphitized porous carbon for lead-carbon batteries with a particle size D50 of 7.2 μm is obtained.
[0047] Example 6
[0048] The rest is the same as Example 1, except that: in step (S1), the mass ratio of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester in the impregnation solution is 100:40:35:3, and finally a biomass graphitized porous carbon for lead-carbon batteries with a particle size D50 of 7.3 μm is obtained.
[0049] Example 7
[0050] The rest is the same as Example 1, except that: in step (S1), coconut shell is used instead of rice shell, and 1-ethyl-3-methylimidazolium tetrachloroferrate is used instead of 1-butyl-3-methylimidazolium tetrachloroferrate; in step (S2), the heat treatment temperature is 1800°C, and finally a biomass graphitized porous carbon with a particle size D50 of 7.5 μm for lead-carbon batteries is obtained.
[0051] Comparative Example 1
[0052] The rest is the same as Example 1, except that: in step (S1), imidazolium tetrachloroferrate is not added, that is, the impregnation solution is a mixed aqueous solution of phosphoric acid, ferrate, and polyoxyethylene fatty acid ester.
[0053] Comparative Example 2 100:10:30:1
[0054] The rest is the same as Example 1, except that: in step (S1), 1-butyl-3-methylimidazolium tetrachloroferrate is 10 parts (that is, the mass ratio of phosphoric acid, 1-butyl-3-methylimidazolium tetrachloroferrate, potassium ferrate, and penetration enhancer Mai Ze 49 in the impregnation solution is 100:10:45:1).
[0055] Comparative Example 3
[0056] The rest is the same as Example 1, except that: in step (S1), 1-butyl-3-methylimidazolium tetrachloroferrate is 50 parts (that is, the mass ratio of phosphoric acid, 1-butyl-3-methylimidazolium tetrachloroferrate, potassium ferrate, and penetration enhancer Mai Ze 49 in the impregnation solution is 100:50:45:1).
[0057] Application Example 1
[0058] Lead powder, acetylene black, barium sulfate, humic acid, short carbon fiber, H2SO4 (1.28g / cm 3 ) and the biomass graphitized porous carbon for lead-carbon battery prepared in Example 1 are mixed evenly in a mass ratio of 100:0.2:0.6:0.15:0.05:2 (i.e., 2wt% of biomass graphitized porous carbon is added to the conventional negative electrode formula), and then a certain volume of polytetrafluoroethylene (PTFE) emulsion and water are added, and mechanically stirred for 10 hours to form a paste (density of about 4.4g / ml), and the paste is evenly applied to the negative electrode grid, and the negative electrode plate with the paste applied is placed in a constant temperature and humidity chamber, and cured at 50°C for 10 hours (humidity 80%) to prepare a lead-carbon battery negative electrode.
[0059] Application Example 2-7
[0060] Other conditions are the same as those in Application Example 1, except that the biomass graphitized porous carbon for lead-carbon battery is prepared according to Examples 2-7 respectively.
[0061] Comparative Application Examples 1-3
[0062] Other conditions are the same as those in Application Example 1, except that the biomass graphitized porous carbon for lead-carbon battery is prepared according to Comparative Examples 1-3 respectively.
[0063] Results and Analysis
[0064] 1) Structural performance test
[0065] X-ray diffraction spectrum: The X-ray diffraction test was performed on the biomass graphitized porous carbon for lead-carbon battery prepared in Example 1. The spectrum is as follows: Figure 2 shown.
[0066] Specific surface area and pore size determination: The Tristar II 3020 fully automatic specific surface and pore size analyzer of Micromeritics Instrument Corporation of the United States was used to conduct a low-temperature nitrogen adsorption experiment on the biomass graphitized porous carbon for lead-carbon batteries prepared in the examples and comparative examples to determine their specific surface area and pore size distribution. Pores with a diameter less than 2nm are micropores; pores with a diameter in the range of 2 to 50nm are mesopores. The specific data are shown in Table 1, where the pore size distribution of the biomass graphitized porous carbon for lead-carbon batteries prepared in Example 1 is shown in Table 1. Figure 3 shown.
[0067] Determination of nitrogen content: The nitrogen content of the biomass graphitized porous carbon for lead-carbon batteries prepared in the examples and comparative examples was analyzed using a vario EL cube elemental analyzer from Elementar, Germany. The data are shown in Table 1.
[0068] Table 1 Specific surface area and pore size data of biomass graphitized porous carbon for lead-carbon batteries
[0069]
[0070] from Figure 2 From the X-ray diffraction spectrum, it can be seen that there are two peaks at 2θ near 25° and 43°, which correspond to the (002) and (100) crystal planes of graphite carbon, respectively, indicating that the prepared porous carbon has a high degree of graphitization.
[0071] It can be seen from Table 1 that compared with Comparative Examples 1-3, the specific surface area and microporosity of the biomass graphitized porous carbon for lead-carbon batteries prepared in the embodiment of the present invention are significantly improved, with a specific surface area of 1500 m 2 / g or more, the microporosity is more than 25%, the mesoporosity is maintained at 65% to 72%, and the N element is more than 7%. That is, through the preparation method of the present invention in which pore-forming activation and catalytic graphitization are carried out simultaneously, a graphitized porous carbon with a high specific surface area, an appropriate micro-mesopore ratio, and nitrogen atom doping is obtained. A higher microporosity is more beneficial to inhibiting the hydrogen reaction, because in the process of hydrogen evolution reaction, the generated hydrogen is not easy to escape in the micropores, but is easier to escape in the mesopores; at the same time, a higher microporosity and an appropriate mesoporosity give the porous carbon a higher porosity and specific surface area. The pores, especially the mesopores, in the high-porosity carbon can store a large amount of electrolyte, so that when sulfuric acid is blocked from entering the interior from the surface of the plate, the electrolyte in the pores can provide a large amount of H + and HSO4 - , which makes the lead-carbon battery have a higher cycle capacity retention rate; in addition, nitrogen atom doping is more beneficial to the electrochemical performance.
[0072] 2) Electrochemical performance test:
[0073] Hydrogen evolution overpotential polarization curve test: The lead-carbon battery negative electrode prepared in the corresponding application example and comparative application example was tested for hydrogen evolution overpotential polarization curve by an electrochemical tester. A three-electrode system was used, with the lead-carbon battery negative electrode prepared in the application example and comparative application example as the working electrode, the platinum electrode as the counter electrode, the calomel electrode as the reference electrode, the electrolyte as 1.12g / ml sulfuric acid solution, the scanning speed: 5mV / s, the scanning range -0.3v to -1.5v. The test results are shown in Table 2.
[0074] Battery performance test: The lead-carbon battery negative electrode prepared in the application example and the comparative application example, the conventional positive electrode, and the electrolyte are used to form a battery, and then the battery is subjected to the HRPSoC cycle life test. The test results are shown in Table 2. The HRPSoC cycle life test conditions are: the battery with a 0% state of charge is charged with a 0.1C current to a cut-off voltage of 2.4V, then charged at a constant voltage of 2.4V for 12h, and left for 10min; then discharged with a current of 1C to 50% of the theoretical capacity, that is, 50% SoC; finally, a high-rate charge and discharge cycle is performed, and the cycle process is as follows: charge with a 2C current for 60s, leave for 10s, discharge with a 2C current for 60s, and leave for 10s. The voltage at both ends of the battery is recorded during the charge and discharge cycle. When the discharge voltage reaches the cut-off voltage of 1.7V, the battery fails.
[0075] Table 2 Electrochemical performance
[0076]
[0077] It can be seen from Table 2 that, compared with the comparative application examples, the hydrogen evolution overpotential of the lead-carbon battery negative electrodes prepared in Application Examples 1 to 8 after being assembled into batteries is significantly improved, all of which are above 1.20 V, and the 500 cycle capacity retention rate at 2C under HRPSoC reaches more than 91%, indicating that the biomass graphitized porous carbon prepared by the present invention significantly reduces the hydrogen evolution reaction in the lead-carbon battery, significantly improves the cycle capacity retention rate, and slows down the performance decay of the lead-carbon battery.
Claims
1. A method for preparing biomass graphitized porous carbon for lead-carbon batteries, characterized in that: The following steps are involved: (S1) impregnation: the pretreated biomass is immersed in an impregnation solution, and then granulated and dried in sequence to obtain a preform; the impregnation solution is a mixed aqueous solution of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester prepared in a mass ratio of 100: (25-40): (15-35): (1-3); (S2) heat treatment: heat treating the preform under an inert atmosphere, cooling, washing and drying after the heat treatment to obtain graphitized porous carbon; (S3) oxidation: soaking the graphitized porous carbon in an oxidant solution, rinsing and drying after soaking to obtain an oxidized material; (S4) Surface modification: The oxidizing material is mixed with melamine polyphosphate, heat-treated in an ammonia atmosphere, and then cooled and ground to obtain biomass graphitized porous carbon for lead-carbon batteries.
2. The preparation method according to claim 1, characterized in that: In step (S1), the impregnation solution is a mixed aqueous solution of phosphoric acid, imidazolium tetrachloroferrate, ferrate, and polyoxyethylene fatty acid ester prepared in a mass ratio of 100: (25-35): (20-30): (1-3).
3. The preparation method according to claim 1, characterized in that: In step (S1), the imidazolium tetrachloroferrate is at least one of 1-butyl-3-methylimidazolium tetrachloroferrate and 1-ethyl-3-methylimidazolium tetrachloroferrate.
4. The preparation method according to claim 1, characterized in that: In step (S1), the ferrate is at least one of potassium ferrate and sodium ferrate; the polyoxyethylene fatty acid ester is at least one of polyoxyethylene ferrate 49 or polyoxyethylene ferrate 52.
5. The preparation method according to claim 1, characterized in that: In step (S1), the pretreatment is to crush, wash and dry the biomass in sequence; the biomass is at least one of coconut shell, rice shell and walnut shell; and / or The dosage ratio of the pretreated biomass to the impregnation liquid is 1 kg: (4-8) L, and the concentration of the impregnation liquid is 25-40 wt %; the impregnation conditions are: temperature 60-80° C., time 2-4 h.
6. The preparation method according to claim 1, characterized in that: In step (S2), the inert atmosphere has an oxygen content of less than 0.1%; the heat treatment conditions are: heating to 1300-1800°C at a heating rate of 5-10°C / min in a graphitization furnace, and keeping warm for 2-4 hours; the washing is boiling in water for 30-60 minutes; the drying is drying to a moisture content of <5wt%, such as baking in an oven at 80-120°C for 24-36 hours.
7. The preparation method according to claim 1, characterized in that: In step (S3), the oxidant solution is 10wt% to 20wt% hydrogen peroxide or an oxidizing inorganic strong acid, and the oxidizing inorganic strong acid is 3 to 5 mol / L nitric acid and / or sulfuric acid.
8. The preparation method according to claim 1, characterized in that: In step (S3), the amount ratio of the graphitized porous carbon to the oxidant solution is 100g: (500-1000)mL; the soaking conditions are: temperature 40-60°C, time 2-6h; the rinsing is washing with water to neutrality; the drying is drying to constant weight.
9. The preparation method according to claim 1, characterized in that: In step (S4), the mass ratio of the oxidizing material to the melamine polyphosphate is 100:(4-8).
10. The preparation method according to claim 1, characterized in that: In step (S4), the heat treatment conditions are: ammonia is introduced into a horizontal induction furnace, the temperature is increased to 850-950°C at a heating rate of 3-8°C / min, and the temperature is kept for 2-4 hours; the grinding is performed by using a jet grinder, and the particle size D50 after grinding is 6-10 μm.
Citation Information
Patent Citations
Preparation method and application of biomass graphitized porous carbon material
CN107265436A